2022
DOI: 10.3390/su142316202
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Fiscal Self-Sufficiency Enables Local Governments to Better Improve the Environmental Governance—Evidence from China’s Lower-Pollution Areas

Abstract: With the rapid development of industrial economy, local governments in China have invested a large amount of financial funds in environmental protection. In the era of widespread use of clean energy, local governments have a greater responsibility to coordinate fiscal policies with industrial development policies to improve regional environment. Local governments with large fiscal surpluses would make more efforts to improve environmental efficiency, rather than attract heavily polluting industrial enterprises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Some scholars concluded that ER does not foster sustainable development of enterprises based on manufacturing industries in 17 European countries and private enterprises in China [12,13]. Lastly, for the policy outcomes of the NEL, the research mainly concentrates on environmental information disclosure, technological innovation, and environmental governance behavior [14][15][16]. The findings of some scholars confirm that the NEL can bring more benefits to enterprises; for example, some scholars found from the perspective of the administrative level of the actual controller and the relationship between the government and the enterprise that the NEL significantly improves the quality of environmental disclosure of the enterprises in the areas with high regulatory intensity and high degree of marketization [17].…”
Section: Discussion Of Literaturementioning
confidence: 99%
“…Some scholars concluded that ER does not foster sustainable development of enterprises based on manufacturing industries in 17 European countries and private enterprises in China [12,13]. Lastly, for the policy outcomes of the NEL, the research mainly concentrates on environmental information disclosure, technological innovation, and environmental governance behavior [14][15][16]. The findings of some scholars confirm that the NEL can bring more benefits to enterprises; for example, some scholars found from the perspective of the administrative level of the actual controller and the relationship between the government and the enterprise that the NEL significantly improves the quality of environmental disclosure of the enterprises in the areas with high regulatory intensity and high degree of marketization [17].…”
Section: Discussion Of Literaturementioning
confidence: 99%
“…Tax revenues create their own income potential and financial autonomy, which may drive structural transformation (Satoła et al, 2019), also aimed at environmental protection policy. Gu et al (2022) found that strong financial resources have significant positive effects on the efficiency of environmental governance at the local level. However, Phillips and Strickland (2016) assumed an inverse relationship between the share of tax revenues in total revenues and environmental action, which was not confirmed in the regression.…”
Section: Oecdmentioning
confidence: 99%
“…According to the median fiscal self-sufficiency rate of the cities where the enterprises are registered, the samples were divided into high fiscal self-sufficiency rates and low fiscal self-sufficiency rates. Referring to Gu et al (2022) [59], the fiscal self-sufficiency rate was defined as the ratio of local fiscal revenue to expenditure. The regression results of enterprises located in cities with high fiscal self-sufficiency rates are shown in column (3) of Table 8.…”
Section: Fiscal Self-sufficiency Ratementioning
confidence: 99%